Can vulnerability and agency co-existin the presence of violence? - Hanzline R. Davids; Eugene Lee Davids (The Thinker)
Children and adolescents in South Africa find themselves in contexts where experiences of and exposure to violence are prevalent. The experiences of violence often perpetuate feelings of vulnerability among adolescents. Vulnerability means exposure to more risks than peers, which is linked to diminished health and well-being. A plethora of understandings related to the complexities and richness of vulnerability exists within the body of knowledge. Kate Brown (2015) contours these complexities and richness of vulnerability across five subthemes/subtypes, namely, innate, situational, social disadvantage, universal, and risk vulnerability. Brown’s understanding of situational vulnerability is used in this study to examine whether vulnerability, in the context of violence, co-exists with agency among adolescents. The study included a sample of 16 adolescents who were purposefully sampled from two secondary schools in the Western Cape. Data were collected using semi-structured interviews that were guided by vignettes and were analysed using thematic analysis. The themes generated from the data tell the story that vulnerability and agency co-exist in the context of violence for adolescents. Agency is displayed in the capacity to make decisions in difficult situations. The decision-making styles displayed were consultative, evaluative, reflective, and considered decision making when faced with challenging circumstances. The findings extend current discussions around the experiences of vulnerability and agency among children and adolescents.